1998
DOI: 10.1177/1045389x9800900810
|View full text |Cite
|
Sign up to set email alerts
|

Idealized Hysteresis Modeling of Electrorheological and Magnetorheological Dampers

Abstract: The hysteresis behavior of a linear stroke magnetorheological damper is characterized for sinusoidal displacement excitation at 2.0 Hz (nominal). Four different modeling perspectives are discussed for purposes of system identification procedures, including: (1) equivalent viscous damping, (2) nonlinear Bingham plastic model, (3) nonlinear biviscous model, and (4) nonlinear hysteretic biviscous model. By progressively adding model parameters with which to better represent pre-yield damper behavior, the force vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
164
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(165 citation statements)
references
References 11 publications
0
164
0
1
Order By: Relevance
“…Gamato and Filisko [56] proposed a parametric viscoelastic-plastic model based on the Bingham model. Wereley et al [7] developed a nonlinear hysteretic biviscous model, which is an extension of the nonlinear biviscous model having an improved representation of the pre-yield hysteresis. However, these models can not readily capture the force roll-off in the low velocity region that is observed in the experimental data.…”
Section: Dynamic Modeling Of Mr Dampersmentioning
confidence: 99%
“…Gamato and Filisko [56] proposed a parametric viscoelastic-plastic model based on the Bingham model. Wereley et al [7] developed a nonlinear hysteretic biviscous model, which is an extension of the nonlinear biviscous model having an improved representation of the pre-yield hysteresis. However, these models can not readily capture the force roll-off in the low velocity region that is observed in the experimental data.…”
Section: Dynamic Modeling Of Mr Dampersmentioning
confidence: 99%
“…Perhaps the most significant of these departures involves the nonNewtonian behavior of MR fluids in the absence of a magnetic field Kormann et al (1994). Moreover, it has been reported that linear stroke MR dampers can show highly nonlinear hysteretic behavior under harmonic loading conditions, that is different from that of the Bingham model Spencer et al (1997), Pang et al (1998), and Wereley et al (1998).…”
Section: Fig 3 An Elementary Hysteresis Operatormentioning
confidence: 99%
“…The utilization of MRFs has been increasing in the different semi-active damping control applications in the low to moderate frequency ranges, including automotive suspension 28 , civil structures [29][30][31][32] , fluid clutches 33 , optical polishing 34 and a variety of aerospace applications [35][36][37][38] , vibration isolation 39,40 , automobile valves 41 and automotive damping applications 42 . Lord Corporation, the leading supplier of commercially proven MR fluids, devices and systems, manufactures three different MR fluids namely LORD MRF-122EG, LORD MRF-132DG and LORD MRF-140CG (ref.…”
Section: Studies On Mr Fluidsmentioning
confidence: 99%
“…Different strategies for the control of semi-active MR suspensions have been published [52][53][54] . Many models were formulated to characterize the dynamic behaviour of MRFDs: The Bingham model 55 ; the bi-viscous hysteresis model 38 and the phenomenological Bouc-Wen model 50 . Among these models, the one that describes well not only the bi-viscous behaviour but also the hysteretic behaviour of MRFDs is the Bouc-Wen model (Figure 3).…”
Section: Modelling Of Mr Dampersmentioning
confidence: 99%